Assessment of the Impacts of Climate Change on Maize Production in the Southern and Western Highlands Sub-agro Ecological Zones of Tanzania - Luhunga, Philbert M. (Frontiers in Environmental Science, 2017)
The Intergovernmental Panel on Climate Change (IPCC) fourth assessment report confirmed that climate change is unequivocal. It is coming to us faster with larger impacts and bigger risks than even most climate scientists expected as recently as a few years ago. One particular worry is the disastrous consequence to agriculture and food security sectors in many parts of the world, particularly in developing countries. Adaptation is the only option to reduce the impacts of climate change on the agriculture sector. However, before planning adaptation policy or strategies to climate change, it is important to assess the impacts of climate change at regional and local scale. In this study the impacts of climate change on rain-fed maize (Zea Mays) production in the southern and western highlands sub-agro ecological zones of Tanzania are evaluated. High resolution climate simulations from the Coordinated Regional Climate Downscaling Experiment _Regional Climate Models (CORDEX_RCMs) were used as input into the Decision Support System for Agro-technological Transfer (DSSAT) to simulate maize yields in the historical climate condition (1971-2000), current (2010-2039), mid (2040-2069) and end (2070-2099) centuries. Daily rainfall, solar radiations, minimum and maximum temperatures for the historical (1971-2000) climate condition and future climate conditions (2010-2099) under two Representative Concentration Pathways (RCPs) RCP4.5 and RCP 8.5 were used to drive DSSAT. The impacts of climate change were assessed by comparing the average maize yields in historical climate condition against the average of simulated maize yields in the current, mid and end centuries under RCP4.5 and RCP8.5. Results indicated that maize yields will decline in future climate condition. High decreases in maize yield over the Southern and southwestern sub ecological zones are expected in the end centuries under RCP 8.5. The main reason for decline in maize yields during future climate is the increase in temperatures that shorten the length of growing seasons. Therefore it is recommended that more studies need to be carried out that addresses on how farmers may adapt the impacts of projected increase in temperatures on maize crop production.